Os objetos da memória episódica : um caminho para o embate entre continuístas e descontinuístas - Cavalcante, Matheus Vinícius (2021)
This dissertation research aims to propose that a philosophical discussion about the content of episodic memory can provide paths for the debate between continuityists and discontinuists, that is, if we resolve the debate about what constitutes episodic memory, we can find ways to the discussion of the relationship between episodic memory and imagination. For this, we will pay attention, in the first chapter, to the panoramic discussion about the main concepts of the current Philosophy of Memory and the theories that stand out in an attempt to describe the act of remembering episodically, thus, I will conclude that the theory of mental time travel together with a theory of simulation it presents the most promising in relation to the causal theory of memory. In the second chapter, after acquiring the most fundamental notions of Philosophy of Memory, we will analyze the theories that dispute the best description of the content of episodic memory; I will consider at the end that, between indirect realism, simulation representationalism, direct realism and hybrid theory, a conception that better describes the content of episodic memory is simulation representationalism. Finally, the third chapter will present continuity and discontinuist arguments from a perspective based on simulation theory and simulation representationalism. I argue in the third chapter that simulation theory and simulation representationalism favor continuism, however, two discontinuist arguments weaken moderate continuism, so I propose a weaker version of continuism that I call weak continuism. I conclude that weak continuism is a good alternative to the debate between continuism and discontinuism, in addition, I suggested that it is necessary to pay attention to expectations about the imagination in order to obtain a more qualified debate between continuism and discontinuism.